Catheter ablation with ethanol infusion in the vein of marshall for persistent atrial fibrillation: safety and procedure duration. (24th May 2021) - Massoulie, G; Andronache, M; Pastorcici, A; Dauphin, C; Costea, A; Blendea, D; Catalan, PA; Lizet, T; Jean, F; Eschallier, R; Puiu, M; Rosu, R; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Ethanol Infusion in the Vein of Marshall (EIVOM) has been recently introduced as an efficient technique that helps achieving mitral isthmus block during ablation procedures for persistent atrial fibrillation (PAF) or peri-mitral atrial flutter. Purpose: We have evaluated the safety of EIVOM and the duration required to perform this procedure. Methods We performed EIVOM in 121 patients for PAF (mean age of 65 years (range 40-83, 73% men; Mean EF 50%. The main steps of the EIVOM were as follows: the procedure commenced with catheterization of the coronary sinus, followed by the subsequent introduction of an angiography catheter that allowed for iodine contrast injection and vein of Marshall (VOM) localization, 1.5-2.5 mm angioplasty balloon over 0.014" guidewire placement and finally the ethanol injection up to 10 ml. Results: No major complications were observed during the ablation procedure or before hospital discharge. In 62 patients in whom procedure duration data was available the mean EIVOM procedure time was 41 min (range from 13 to 105 min). After the first 20 procedures, where the learning curve for the operators has to be taken into consideration, a reduction in the time required to achieve EIVOM was consistently noted, with an average of less than 30 min. and for the last 20 procedures less than 20 min. Factors which increase the time required for successful EIVOM include: difficulty in visualizing the ostium of the VOM, a VOM ostium located proximally, difficulty in advancing the angioplasty wire into the VOM and balloon displacement and repositioning. Conclusions: Ethanol infusion in the Vein of Marshall is a safe and efficient technique that can be performed in an acceptable amount of time after an initial learning curve.